Soil characterization for seismic vulnerability and preliminary subsidence assessment based on microtremor analysis in Sukarame District, Bandar Lampung - Antosia, Risky Martin; Endryanti, Windy Meylana; Farduwin, Alhada; Rizki, Reza; Styawan, Yudha (Brawijaya University, 2026)
This research estimated soil properties and land stability in Sukarame District, Bandar Lampung, using multi-parameter microtremor-derived H/V spectral ratio (HVSR) values and spaceborne InSAR deformation data. The study area is mainly composed of unconsolidated Quaternary volcanic deposits with an average natural frequency ( ) of about 2 Hz and a moderate amplification factor ( ) value of 4. Such parameters, together with an average seismic vulnerability index ( ), of 11s strongly point to substantial impedance contrasts in the sediments and a large overall sediment thickness. To validate the physical effects of these features, a Multi-Temporal InSAR analysis was applied using satellite observations. Results showed a strong land subsidence rate, with a difference in distance from the satellites up to -25 cm for certain sectors. Spatially problematic zoning corresponded to the area with higher near-surface stiffness ( ranges of 400-470 m/s) along the territories with large subsidence rates. This relationship showed that higher. and shallow material solidness are not sufficient conditions for stability against vertical deformation (also referred to as settlement), as substantial consolidation is likely to result from the significant load applied to the soil and groundwater extraction due to population pressure in these urban areas. These results highlight that must be used with caution and interpreted in conjunction with geodetic data for an integrated stability analysis. This integrated model is useful as a general guideline for land stability management, infrastructure hazard preparedness, and disaster-resilient spatial planning in the rapidly developing Sukarame District.